Solar Power to the People - Jos Boere (IOS Press, 2018)
You read about it every day: How can we create a sustainable, reliable and affordable energy supply? Does a local water supply play a role in this? Why don't we drive hydrogen cars that are powered by the sun and rain? The availability of cheap green energy is increasing. . We have solar and wind power, and even energy derived from ambient heat. At the same time we have very diverse energy needs: fuel for cars, electricity, heat for buildings, feedstock for industrial processes, to name just a few. Energy supply and demand do not match, which means that we have to match resources, storage and consumption in an intelligent way. Solar Power to the People casts a thoughtful vision on sustainable energy. We have to bring the power of the sun to the people. That is what sustainable energy and water is all about. The authors believe we have to act quickly. The matter is urgent.